Left-right confusion in psychiatric, neurodevelopmental and neurological disorders: A systematic review - Moritz Thaler; Sebastian Ocklenburg (Brain Research Bulletin)
Left-right confusion is common in healthy individuals, but increased prevalence has been reported in several psychiatric, neurodevelopmental, and neurological disorders. The present systematic review aimed to identify disorders in which the prevalence of left-right confusion is higher than in the general population. For this purpose, a systematic review following PRISMA guidelines was conducted using the databases Google Scholar, PubMed, and Mendeley. A total of 20 quantitative case-control studies were included. Lesions in parietal brain areas and damage to temporal-parietal-occipital brain areas because of Alzheimer's disease were associated with severe impairments in left-right orientation. Furthermore, evidence for developmental impairments in direction assignment was provided by studies on developmental topographical disorientation (DTD). These DTD-related impairments are associated with low functional connectivity between the hippocampus and the right prefrontal cortex. Individuals with DTD show significantly poorer performance in direction discrimination compared to healthy subjects. In addition, the review highlights that, despite previous research, there remains a substantial need for further studies and for the development of a uniform definition and operationalization of left-right confusion in clinical populations.